Properties of compressed banana fiber composite from agriculture waste using cold-setting adhesives - Siti Noraisya Abdul Rohni (2014)
In this study, banana fibers have been used as reinforcement in epoxy resins to produce compressed banana fiber composite. The aim of this study is to compare the mechanical and physical properties of the banana fiber composite according to the portions of the banana stem fiber. The method used in fabrication of banana fiber composite is cold-press. This method was proposed to ease the production of this compressed banana fiber composite by the most people with different economic background. Physical testing of compressed banana fiber were moisture content and density. The compressed banana fiber composite were mechanically tested including bending (flexural), tensile and compression. The physical properties were done to indicate that moisture content and density banana fibers affect the mechanical properties of compressed banana fiber composites. It was describe and explain each research activity based on the standards testing and requirement which had been used in this experimental are based on British Standard (BS 310:1993) standard (EN 319:1993, BS 373:2008 and inhouse method). Moisture content of the banana fibers increase up from bottom part to the upper part of the stems while the density shows vice versa. The mechanical test result showed that the bottom part has the highest and strongest value among the three portions. Nishino (2004) discussed that each layer of the banana fibers compose of cellulose embedded with a matrix of hemicellulose and lignin, a structure that is analogous to that of artificial fiber reinforced composites. The bottom part of a plant has the highest cellulose content due to the early development of the plant. The bottom part of the banana stem fiber can produce a highest durability composites panel.